Study of the Influence of Different Optical Properties on the Image of Compound light microscope - Karam, Ghada Sabah (Iraqi Journal of Science, 2022)
Microscope images are characterized by a number of specific parameters, the influence of such parameters (intensity, magnification, numerical aperture, diaphragms aperture, segmentation, and edge detecting technique) on measurement in optical microscope images have been determined with using a powerful image processing methods. As one of the most widespread techniques in biological investigation and dynamic process, light compound microscopy has used to analyze the optical properties of biological images. The results indicate that a wide aperture allows maximum resolution and depth of field, but decreases the contrast. While a small aperture improve visibility and contrast but decreases the resolution. The results also show the best performance in focus with image that have a wide diaphragm aperture at high intensity. The analysis of statistical properties of images is acceptable, and there is unnoticeable changes in correlation coefficients between images at high intensity.